FAKTOR–FAKTOR YANG MEMPENGARUHI INTEGRITAS LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI) - Marsita Prasetyana, 13.05.52.0202; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2017)
This study examined the effect of the influence of the Audit Committee, Independent Commissioner. Institutional Ownership, Managerial Ownership, Audit Quality and Leverage for the Integrity of Financial Statements on manufacturing companies listed in Indonesia Stock Exchange. The population of this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) during the years 2013-2015. This study using purposive sampling method to collect data. The collection of data from the years 2013 -2015 resulted in 102 samples. Methods of data analysis of this research is multiple regression analysis . The study found that the variable leverage, institutional ownership a significant negative effect on the integrity of financial statements. While the audit committee, independent board, managerial ownership, audit quality does not affect the integrity of financial statements.Keywords: Integrity Financial Statements, Audit Committee, Independent Commissioner, Institutional Ownership, Managerial Ownership, Audit Quality and Leverage